2017
DOI: 10.1038/srep39842
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene oceanic seaways and global climate

Abstract: Tectonically induced changes in oceanic seaways had profound effects on global and regional climate during the Late Neogene. The constriction of the Central American Seaway reached a critical threshold during the early Pliocene ~4.8–4 million years (Ma) ago. Model simulations indicate the strengthening of the Atlantic Meridional Overturning Circulation (AMOC) with a signature warming response in the Northern Hemisphere and cooling in the Southern Hemisphere. Subsequently, between ~4–3 Ma, the constriction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 53 publications
(178 reference statements)
3
74
0
1
Order By: Relevance
“…The warming of the Norwegian Sea at 4.0 Ma coincides with several tectonic shifts that could affect the climate development of the Nordic Seas region. A threshold in the closure of the CAS has been suggested to take place at this time (Karas et al, 2017;Steph et al, 2010), and uplift of Greenland and northern Scandinavia took place (Knies et al, 2014a). Enhanced North Atlantic Deep Water (NADW) production and a more vigorous AMOC have been suggested by Steph et al (2010) towards 4.0 Ma based on benthic δ 13 C in the low-latitude Atlantic.…”
Section: Rapid Warming Followed By Extended Interval Of Highmentioning
confidence: 99%
See 2 more Smart Citations
“…The warming of the Norwegian Sea at 4.0 Ma coincides with several tectonic shifts that could affect the climate development of the Nordic Seas region. A threshold in the closure of the CAS has been suggested to take place at this time (Karas et al, 2017;Steph et al, 2010), and uplift of Greenland and northern Scandinavia took place (Knies et al, 2014a). Enhanced North Atlantic Deep Water (NADW) production and a more vigorous AMOC have been suggested by Steph et al (2010) towards 4.0 Ma based on benthic δ 13 C in the low-latitude Atlantic.…”
Section: Rapid Warming Followed By Extended Interval Of Highmentioning
confidence: 99%
“…A statistically significant increase in global ice volume from 3.6 Ma was noted by Mudelsee and Raymo (2005), who consider this to be the marker for the onset of NHG. Furthermore, a large increase in IRD influx in the North Atlantic (Kleiven et al, 2002), and a crash of productivity in the North Pacific (Haug et al, 2005), indicated an important threshold towards intensified Northern Hemisphere ice build-up at ca. 2.7 Ma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The closure of the Central American Seaway (CAS; Panama) has experienced its most critical phase just during this time interval (Haug et al, ; Haug & Tiedemann, ). The constriction and final closure of the CAS led to the intensification of both the Gulf Stream and, in a broader perspective, the Atlantic Meridional Overturning Circulation, leading to commonly higher sea surface temperatures (SSTs; Haug & Tiedemann, ; Haug et al, ; Karas et al, ) and salinities (Keigwin, ) in the Caribbean sector of the western Atlantic. At the same time, the East Pacific experienced a decline in surface temperatures, the intensification of costal upwelling (Dekens et al, ; Ibaraki, ), and the shoaling of the tropical East Pacific thermocline (Steph et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the East Pacific experienced a decline in surface temperatures, the intensification of costal upwelling (Dekens et al, ; Ibaraki, ), and the shoaling of the tropical East Pacific thermocline (Steph et al, ). Ultimately, the closure of the CAS is thought to have preconditioned the initiation of the Northern Hemisphere glaciation (NHG; Haug & Tiedemann, ; Haug et al, ; Karas et al, ; Lunt et al, ). The Indonesian Gateway is also considered as a major driver of the reorganization of the Plio‐Pleistocene oceanic and climatic system (Cane & Molnar, ; Karas et al, ).…”
Section: Introductionmentioning
confidence: 99%